The Function of cGAS-STING Pathway in Treatment of Pancreatic Cancer - Mohseni, Ghazal; Li, Juan; Ariston Gabriel, Abakundana Nsenga; Du, Lutao; Wang, Yun-shan; Wang, Chuanxin (Frontiers in Immunology, 2021)
The activation of stimulator of interferon genes (STING) signalling pathway has been suggested to promote the immune responses against malignancy. STING is activated in response to the detection of cytosolic DNA and can induce type I interferons and link innate immunity with the adaptive immune system. Due to accretive evidence demonstrating that the STING pathway regulates the immune cells of the tumor microenvironment (TME), STING as a cancer biotherapy has attracted considerable attention. Pancreatic cancer, with a highly immunosuppressive TME, remains fatal cancer. STING has been applied to the treatment of pancreatic cancer through distinct strategies. This review reveals the role of STING signalling on pancreatic tumors and other diseases related to the pancreas. We then discuss new advances of STING in either monotherapy or combination methods for pancreatic cancer immunotherapy.